Development of a virosomal malaria vaccine candidate: from synthetic peptide design to clinical concept validation. (August 2012) - Pluschke, Gerd; Tamborrini, Marco
An ideal malaria vaccine would prevent disease and reduce transmission by targeting several developmental stages of human malaria parasites. To be cost-effective, a modular antigen delivery technology is required for the development of such a multivalent subunit vaccine. In this review, we summarize and discuss a strategy to develop synthetic peptidomimetics of key malaria target antigens for inclusion in a multivalent malaria subunit vaccine based on immunopotentiating reconstituted influenza virosomes. Clinical testing of a bivalent virosomal formulation incorporating two structurally optimized peptidomimetics has demonstrated safety, immunogenicity and pilot efficacy. While this clinical validation supports the concept of using peptide-loaded virosomes for vaccination in humans, it is assumed that additional antigens will have to be added to the bivalent formulation to generate a highly effective malaria vaccine.